Hara kiri (Seppuku) [videorecording (DVD)] - Hashimoto, Shinobu, 1918-2018; Takemitsu, Tōru; Miyajima, Yoshio, 1909-1998; Nakadai, Tatsuya, 1932-; Iwashita, Shima, 1941-; Ishihama, Akira, 1935-2022; Takiguchi, Yasuhiko, 1924-2004 (Criterion collection, 2005)
Peace in 17th-century Japan causes the Shogunate's breakup of warrior clans, throwing thousands of samurai out of work and into poverty. An honorable end to such fate under the samurai code is ritual suicide, or hara-kiri.